Odpowiedzi

2010-03-06T14:14:51+01:00
A) 1/3x-2=x+2
-2/3x=4
x=-6
b) 1-6/7x=4/7
-6/7x=-3/7
6x=3
x=2
c) 6(1/4x-2)=18
3/2x-12=18
3x=30
x=10
d) x/6-1/6=1
x/6=7/6
x=7
e) -2(2x-1)=x/3
-4x+2=x/3
-12x+6=x
-13x=-6
x=6/13
f) 2/5(3-x)=-2
6/5-2/5x=-2
6-2x=-10
-2x=-16
x=8
g) 3/4(2-3x)=-6
6/4-9/4x=-6
6-9x=-24
-9x=-30
x=30/9
h)1/5(x-3)=-6
1/5x-3/5=-6
x-3=-30
x=-27
i) 0,6+x/2=x+1
-x/2=0,4
x=-0,8
1 5 1
2010-03-06T14:33:33+01:00
A) 1/3x- 2= x+ 2
1/3x- x= 2+2
-2/3x= 4/ : (-2/3)
x= -6

b) 1- 6/7x = 4/7
-6/7x= 4/7- 1
-6/7x= -3/7/ : (-6/7)
x= 2

c) 6( 1/4x- 2)= 18
3/2x - 12= 18
3/2x= 18+ 12
3/2x= 30/ : 3/2
x= 20

d) x/6- 1/6=1/ *6
x-1=6
x=7

e) -2(2x-1)= x/3
-4x+2= x/3
-4x- x/3= -2/ *3
-12x- x= -6
-13x= -6/: (-13)
x= 6/13

f) 2/5(3-x)= -2
6/5- 2/5x= -2
-2/5x= -2 - 6/5
-2/5x= -16/5 /: (-2/5)
x= 8

g) 3/4(2-3x)= -6
6/4 - 9/4x= -6
-9/4x= -6 -6/4
-9/4x= - 30/4 /: (-9/4)
x= 30/9

h) 1/5(x-3)= -6
1/5x- 3/5= -6
1/5x= -6+ 3/5
1/5x= -27/5 /: 1/5
x= 27

i) 0,6 + x/2= x+1
6/10 + x/2= x+1 /*2
12/10+ x= 2x+2
x-2x= 2 - 12/10
-x= -1/5 /: (-1)
x= 1/5